2017
DOI: 10.21608/assjm.2017.56852
|View full text |Cite
|
Sign up to set email alerts
|

Application of biofertilization and biological control for cowpea production

Abstract: This study was carried out during two successive seasons 2014 and 2015 for evaluating the effect of inoculation with Bradyrhizobium sp, Bacillus megaterium, Bacillus circulans, Glomus macrocarpum instead a part of chemical fertilization in the presence of biocontrol agent i.e., Pseudomonas fluorescens on some microbial enzymes activity, growth characteristics, some biological constituent as well as yield and its components for optimal nutrition and some attributes of cowpeas. Obtained data showed significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
0
0
Order By: Relevance
“…It was found that inoculation of khella plants with Streptomyces rochei (MA-6) and Bacillus subtilis (MA-13) in combination gave the tallest plants, highest number of branches/ plant and the heaviest herb fresh and dry weights (g)/plant as ranged 17.7 and 18.5, 33.53 and 25.3, 14.3 and 11.9, and 12.9 and 12.8% over control in the first and second seasons, respectively. The positive effect of bio-fertilization on enhancing growth parameters was observed by Hassan et al (2009) on khella plant, Hussein et al (2016), and Kamal and Ashish (2021) on dill (Anethum graveolens L.) plants, Alemu and Alemu (2015), and Somayeh and Hashem (2015) on faba bean (Vicia faba), Hegazi et al (2015) on squash plants. According to the interaction between NPK, bio straw manure and microbial inoculant treatments, it had a significant effect on all growth parameters of khella (Ammi visnaga L.) plants in both seasons.…”
Section: Growth Parametersmentioning
confidence: 98%
See 2 more Smart Citations
“…It was found that inoculation of khella plants with Streptomyces rochei (MA-6) and Bacillus subtilis (MA-13) in combination gave the tallest plants, highest number of branches/ plant and the heaviest herb fresh and dry weights (g)/plant as ranged 17.7 and 18.5, 33.53 and 25.3, 14.3 and 11.9, and 12.9 and 12.8% over control in the first and second seasons, respectively. The positive effect of bio-fertilization on enhancing growth parameters was observed by Hassan et al (2009) on khella plant, Hussein et al (2016), and Kamal and Ashish (2021) on dill (Anethum graveolens L.) plants, Alemu and Alemu (2015), and Somayeh and Hashem (2015) on faba bean (Vicia faba), Hegazi et al (2015) on squash plants. According to the interaction between NPK, bio straw manure and microbial inoculant treatments, it had a significant effect on all growth parameters of khella (Ammi visnaga L.) plants in both seasons.…”
Section: Growth Parametersmentioning
confidence: 98%
“…Moreover, the highest values of the number of umbels per plant, the seed yield per plant (g) and per feddan (kg) were obtained when khella plants were supplied with fertilizer at a high rate (25 m 3 /feddan), as ranged 92.5, 57.6% concerning number of umbels per plant and 42.6 and 44.5% regarding seed yield per plant (g) and per feddan (kg), in the two seasons over the control, respectively. The effectiveness of organic manure on increasing yield parameters was revealed by Hassan et al (2009)…”
Section: Yield Parametersmentioning
confidence: 99%
See 1 more Smart Citation